Comparison of Mortality and Glasgow Outcome Scale Extended (GOSE) between Craniotomy and Decompressive Craniectomy in Patients with Traumatic Acute Subdural Hematoma at Sanglah General Hospital, Bali - Yanti, Ni Luh Putu Julita; Niryana, I Wayan; Maliawan, Sri; Semadi, I Nyoman; Mahadewa, Tjokorda G. B.; Wibawa, I G. A. B. Krisna (JBN (Jurnal Bedah Nasional); Vol 6 No 1 (2022): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2022.v06.i01.p03, 2022)
Background: Craniotomy and decompressive craniectomy and are surgical modalities for the evacuation of acute subdural hematoma (SDH). These two techniques show different outcomes in various existing studies. The superiority between either techniques remains controversial. Objective: To determine the outcome comparison of mortality and Glasgow Outcome Scale Extended (GOSE) craniotomy with decompressive craniectomy in patients with traumatic acute SDH. Methods: This is a historical cohort study. Samples of the study were collected from January 2018 to March 2020 at Sanglah General Hospital. All patients with acute traumatic SDH who underwent SDH evacuation with craniotomy and decompressive craniectomy were assessed for mortality status at discharge and GOSE 3 months after surgery. Independent T-test will be carried out if the numerical variable were all normally distributed, while Mann-Whitney U test will be performed if otherwise. A Chi-square test will be performed on all unpaired categorical variables. Statistical analysis was performed with SPSS 25 with 95% confidence intervals. Results: As many as 40 subjects with traumatic acute SDH who underwent craniotomy and 40 subjects with traumatic acute SDH who underwent decompressive craniectomy were included in this study. There was no significant difference in mortality (RR: 1; 95% CI 0.67-1.87; p=0.651) and GOSE score (p=0.718) in traumatic acute SDH who underwent craniotomy or decompressive craniectomy. Conclusion : There was no difference in mortality and GOSE outcomes between a craniotomy and decompressive craniectomy for management of traumatic acute SDH.